Ultrastructural characterization of tumor necrosis factor alpha receptor type 1 distribution in the hypothalamic paraventricular nucleus of the mouse. (3rd June 2017) - Glass, Michael J.; Chan, June; Pickel, Virginia M.
Highlights: In the PVN, TNFR1 was largely expressed in neuronal profiles, but was also detected in a small population of glia. Within PVN neurons TNFR1 was prominently found in dendrites. TNFR1-labeled dendrites were contacted by axon terminals forming excitatory and inhibitory synapses. TNFR1 is strategically positioned for modulation of excitatory and inhibitory transmission in the PVN. Abstract: The immune/inflammatory signaling molecule tumor necrosis factor α (TNFα) is an important mediator of both constitutive and plastic signaling in the brain. In particular, TNFα is implicated in physiological processes, including fever, energy balance, and autonomic function, known to involve the hypothalamic paraventricular nucleus (PVN). Many critical actions of TNFα are transduced by the TNFα type 1 receptor (TNFR1), whose activation has been shown to potently modulate classical neural signaling. There is, however, little known about the cellular sites of action for TNFR1 in the PVN. In the present study, high-resolution electron microscopic immunocytochemistry was used to demonstrate the ultrastructural distribution of TNFR1 in the PVN. Labeling for TNFR1 was found in somata and dendrites, and to a lesser extent in axon terminals and glia in the PVN. In dendritic profiles, TNFR1 was mainly present in the cytoplasm, and in association with presumably functional sites on the plasma membrane. Dendritic profiles expressing TNFR1 were contacted by axon terminals, which formed non-synaptic appositions, as well as excitatory-type and inhibitory-type synaptic specializations. A smaller population of TNFR1-labeled axon terminals making non-synaptic appositions, and to a lesser extent synaptic contacts, with unlabeled dendrites was also identified. These findings indicate that TNFR1 is structurally positioned to modulate postsynaptic signaling in the PVN, suggesting a mechanism whereby TNFR1 activation contributes to cardiovascular and other autonomic functions.